Blockade of Apoptosis Signal-Regulating Kinase 1 Attenuates Matrix Metalloproteinase 9 Activity in Brain Endothelial Cells and the Subsequent Apoptosis in Neurons after Ischemic Injury - Cheon, So Y.; Cho, Kyoung J.; Kim, So Y.; Kam, Eun H.; Lee, Jong E.; Koo, Bon-Nyeo (Frontiers in Cellular Neuroscience, 2016)
Conditions of increased oxidative stress including cerebral ischemia can lead to blood-brain barrier (BBB) dysfunction via matrix metalloproteinase (MMP). It is known that MMP-9 in particular is released from brain endothelial cells is involved in the neuronal cell death that occurs after cerebral ischemia. In the intracellular signaling network, apoptosis signal-regulating kinase 1 (ASK1) is the main activator of the oxidative stress that is part of the pathogenesis of cerebral ischemia. ASK1 also promotes apoptotic cell death and brain infarction after ischemia and is associated with vascular permeability and the formation of brain edema. However, the relationship between ASK1 and MMP-9 after cerebral ischemia remains unknown. Therefore, the aim of the present study was to determine whether blocking ASK1 would affect MMP-9 activity in the ischemic brain and cultured brain endothelial cells. Our results showed that ASK1 inhibition efficiently reduced MMP-9 activity in vivo and in vitro. In endothelial cell cultures, ASK1 inhibition upregulated phosphatidylinositol 3-kinase (PI3K)/Akt/nuclear factor erythroid 2 [NF-E2]-related factor 2 (Nrf-2)/heme oxygenase-1 (HO-1) signals and downregulated cyclooxygenase-2 (Cox-2) signals after hypoxia/reperfusion. Additionally, in neuronal cell cultures, cell death occurred when neurons were incubated with endothelial cell-conditioned medium (EC-CM) obtained from the hypoxia/reperfusion group. However, after incubation with EC-CM and following treatment with the ASK1 inhibitor NQDI-1, neuronal cell death was efficiently decreased. We conclude that suppressing ASK1 decreases MMP-9 activity in brain endothelial cells, and leading to decreased neuronal cell death after ischemic injury.